Property Inheritance Management Issues Unclaimed Property - Abu Bakar, Azizi; Mohamad Rapi, Muhammad Ashraf Aliff; Sallehuddin, Mohd Rashdan (University of Tehran, 2020)
Unclaimed property is a major issue in Malaysia. It is also a disadvantage to the Islamic economy because wealth cannot be exploited. It continues to grow year by year and it does not appear that it will be completed in a short time. This article discusses issues affecting the increase of unclaimed property and the authorities involved in resolving these endless issues. In addition to issues of public awareness, social issues and administrative and legal issues, educational level also plays a significant role in contributing to the increase in unclaimed property as the availability of education on this property will provide awareness and smart people to act to prevent frozen inheritance. Therefore, this artwork provides an overview of related issues and provides steps to be taken to mitigate the increase in unclaimed property